On the structure of cyclic codes over the ring Z2s[u]∕〈uk〉 - Hai Q. Dinh (2018)
© 2018 Elsevier B.V. In this paper, we consider cyclic codes of odd length n over the local, non-chain ring R=Z2s[u]∕〈uk〉 = Z2s+uZ2s+…+uk−1Z2s(uk=0), for any integers s≥1 and k≥2. An explicit algebraic representation of such codes is obtained. This algebraic structure is then used to establish the duals of all cyclic codes. Among others, all self-dual cyclic codes of odd length n over the ring R are determined. Moreover, some examples are provided which produce several optimal codes.